Design of RT/RW Portal Public Service Applications to Build a Technology Literate Society in the Era of Society 5.0 - Febri Dolis Hediani (Knowbase : International Journal of Knowledge in Database, 2022)
The role of RT/RW administrators is not only as administrative public servants but also as a servant to the interests of the wider community. Therefore, their role needs to be optimized so that the aspirations of the citizens can be accommodated. However, the large area and dense population often make RT/RW administrators constrained in accelerating access to services and increasing the effectiveness of their activities. The role of information technology is very important, considering that the use of technology has been proven to be successful in improving public services. The utilization of an existing information system is not necessarily in accordance with the needs and related regional policies. In this study, the development of a system adapted to the needs and regional policies, especially in Sekeloa Village, Coblong District, Bandung City was carried out. An RT/RW Portal application was produced which has five main features, namely reporting events, invitations to activities, voting, transparency of funds, and printing reports. This application development method uses the SDLC (Software Development Life Cycle) method with stages of data requirements analysis, software design and design, application development (programming) and application testing before being implemented in RT-RW. The results obtained are in the form of an RW portal application that can assist the function and role of the RT/RW both in administrative management, as well as the dissemination of information in the form of news on activities surrounding the RT/RW. The conclusion is that the API of this application can be developed to build mobile.